Severe ARDS due to disseminated toxoplasmosis in a person with HIV successfully treated with ECMO: a case report - Daniel Medina; Renzo Ávila; Graciela Rodríguez-Sevilla; Víctor Gumucio; María Bonilla; Gabriela Abelenda-Alonso; Jordi Niubó; Maria Saumoy; Juan Tiraboschi; María Paz Fuset; Arkaitz Imaz (Frontiers in Medicine)
Disseminated toxoplasmosis (DT) is an uncommon but severe complication associated with acquired immunodeficiency syndrome (AIDS). This case report describes the successful treatment of a 28-year-old male individual with AIDS who developed severe and life-threatening acute respiratory distress syndrome (ARDS) resulting from DT, in which extracorporeal membrane oxygenation (ECMO) was employed effectively.